Spatiotemporal variation in the endangered Thymus decussatus in a hyper-arid environment - Thompson, Katy; Gilbert, Francis (Oxford University Press, 2015)
Aims: Arid environments are resource limited, with scarcity of water the key limiting factor, but hyper-arid environments are rarely studied. We test for spatial and temporal variation in ecologically important characteristics to deduce plant adaptations to the extreme climate. Methods: The endangered Sinai Thyme (Thymus decussatus) exists as a set of patches on mountaintops within the St Katherine Protectorate, South Sinai, a hyper-arid environment with rare events of good rains (every 10–15 years). Important Findings: From spatial and temporal patterns of plant mortality, size, condition and flowering among 10 patches on the Mt Sinai massif, we deduce that the incidence and amount of flowering responds relatively quickly (1–2 years) to rainfall fluctuations, but plant growth respond only very slowly. Small individuals are most at risk of death during drought, and a high proportion of plants were dead at the end of 8 years of very low or no rainfall. No recruitment of seedlings was observed even in years of good rainfall. Droughts are expected to become increasingly frequent due to climate change; this may have important consequences for Sinai Thyme and also its associated herbivores, such as the Critically Endangered Sinai Baton Blue (Pseudophilotes sinaicus) whose larval stage feeds exclusively upon the flowers of this plant.